Restrukturisasi Organisasi Bidang Farmasi Dinas Kesehatan Provinsi Sulawesi Utara - Mengko, Laura Evilientje; Kaunang, Markus; Londa, Very Y. (JURNAL ILMIAH SOCIETY, 2015)
Implementation of health services in North Sulawesi province level through the Pharmaceutical and Medical Devices that are structurally no longer / not stand alone as a field service or sexy but melted in a particular field. This research aims to study and analyze the organizational restructuring of the Department of Health Pharmaceutical Sector North Sulawesi Provensi henceforth expected to enter the development of the science of public administration management.The conclusion of this study is the organizational restructuring of pharmaceutical department of North Sulawesi Provincial Health Office has not performed well based on the structure and organizational processes through the provision of additional duty in the Field of Health Care Development Efforts in the current structure handles pharmacy services. Recommendations research iniyaitu communication and coordination with relevant agencies in handling pharmaceuticals and as rare fore need to make structural changes to restore the fields of pharmaceuticals, food and beverages on the structure of the health department.Keywords: Organizational Restructuring, Pharmacy, Structure, Work Process.